Characteristics of the histamine release from hamster cheek pouch mast cells stimulated by lectins from Brazilian beans and concanavalin A - Ferreira, Rosana Rossi [UNESP]; Cavada, B. S.; Moreira, R. A.; Oliveira, J. T A; Gomes, J. C. (Springer Nature, 1996)
We have characterized the histamine releasing effects of lectins extracted from Brazilian beans, in comparison to concanavalin A, in hamster cheek pouch cell suspensions containing mast cells. The lectins from Dioclea virgata, Canavalia brasiliensis, and Dioclea rostrata induce histamine release in a similar manner to concanavalin A, but appear to differ in potency and efficacy. The effects depended on the temperature, pH, and metabolic energy, demonstrating the non-cytotoxic nature of the histamine release. It is suggested that the lectins studied act by the same mechanism as concanavalin A (interacting with sugars in the antibodies bound to the mast cells), since high concentrations of glucose inhibit the histamine release. The lectins at high concentrations quench the histamine release. This suppression is reversed by increasing calcium concentration, suggesting that the lectins bind to the calcium that is essential for the secretion, thereby confirming and extending our previous data using the lectin from Dioclea virgata in rat peritoneal mast cells.
Keywords: Cheek pouch; Hamster; Histamine release; Lectins; Mast cells; antibody; calcium; concanavalin a; glucose; histamine; lectin; animal experiment; animal tissue; antigen antibody reaction; bean; cheek pouch; controlled study; female; hamster; histamine release; male; mast cell; metabolism; nonhuman; peritoneum mast cell; ph; temperature; Animals; Cheek; Concanavalin A; Cricetinae; Female; Histamine Release; Hydrogen-Ion Concentration; Male; Mast Cells; Mouth Mucosa; Phosphatidylserines; Temperature